Eksplorasi Model SERVQUAL sebagai Basis Penilaian Kualitas Layanan Haji dan Tingkat Kepuasan Jemaah - Ngatijah, Siti; Setiawan, Agus; Kusno Aji N, Didik; Ligery, Finny (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine the extent to which service quality influences the satisfaction of hajj pilgrims in Mesuji Regency during the 2022–2023 period, using the five SERVQUAL dimensions: reliability, responsiveness, assurance, empathy, and tangibles. A quantitative survey approach was employed, involving 46 pilgrims as respondents. Data analysis included validity and reliability testing, classical assumption tests, and multiple linear regression to evaluate both the simultaneous and partial effects of each service quality dimension. The findings demonstrate that service quality has a significant and substantial impact on pilgrims’ satisfaction. Simultaneously, all five dimensions significantly influence satisfaction, as indicated by an F-value of 20.160 with a p-value of 0.000. The model’s coefficient of determination (R² = 0.716) indicates that 71.6% of the variance in satisfaction is explained by the service quality variables. Partially, the reliability and empathy dimensions are the most influential predictors, revealing that accuracy, procedural consistency, and personalized attention are the aspects most strongly perceived by pilgrims in enhancing their satisfaction. Meanwhile, responsiveness, assurance, and tangibles also contribute to satisfaction but to a lesser degree. These findings highlight the need to prioritize improvements in reliability and empathy to strengthen the overall quality of hajj service delivery.